Zodorís Califatidis y la ventana del ladrón o de cómo la autotraducción le hace a uno menos extranjero (TEST Ticontre. Theory Text Translation, 2017)
Theodor Kallifatides was born in Greece in 1938. Disappointed at his country, he migrated to Sweden in 1964, where he decided to stay. He started writing in Swedish and he has received plentiful literary awards for his works. After some time he started writing in Greek as well and self-translating his books, first from Greek to Swedish, and lately from Swedish to Greek.Kallifatides feels the need to write about his own experience as a migrant. In his autobiographical novel Μια νέαπατρίδα έξω από το παράθυρο μου (2002) [A New Homeland Outside My Window], he admits that he writes to find out who he really is. He speaks openly about his ‘xenitia’ (or longing for home) and admits that when he stopped being a foreigner in his adoptive country, he started feeling like a foreigner to himself. His mother tongue comes then to the rescue and with it, self-translation.